2015
DOI: 10.2308/acch-51105
|View full text |Cite
|
Sign up to set email alerts
|

U.S.-Listed Foreign Companies' Choice of a U.S.-Based versus Home Country-Based Big N Principal Auditor and the Effect on Audit Fees and Earnings Quality

Abstract: SYNOPSIS We examine why U.S.-listed foreign companies choose to have a U.S.-based (rather than home country-based) Big N firm as their principal auditor for SEC reporting purposes and the effects of that choice for audit fees and earnings quality. We find that the likelihood of the Big N principal auditor being U.S.-based is decreasing in client size and the level of investor protection in the home country, and increasing in the proportion of income earned outside the home country. We also find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 63 publications
2
19
0
Order By: Relevance
“…Hope et al () found that this negative association is also mitigated by the firms' international operations. This is consistent with the argument that (1) secrecy is related negatively to firm‐level disclosures (Gray & Vint, ) and (2) the level of internationalization increases the likelihood of hiring high‐quality auditors (Asthana et al, ; Tsao et al, ). Although the documented negative association supports a demand‐side view, it is not clear how the “supply of audit services” will be affected by the cultural value of secrecy.…”
Section: Determinants Of Auditor Choicesupporting
confidence: 87%
See 4 more Smart Citations
“…Hope et al () found that this negative association is also mitigated by the firms' international operations. This is consistent with the argument that (1) secrecy is related negatively to firm‐level disclosures (Gray & Vint, ) and (2) the level of internationalization increases the likelihood of hiring high‐quality auditors (Asthana et al, ; Tsao et al, ). Although the documented negative association supports a demand‐side view, it is not clear how the “supply of audit services” will be affected by the cultural value of secrecy.…”
Section: Determinants Of Auditor Choicesupporting
confidence: 87%
“…The different legal environments related to investor protection could determine the governance functions of auditors. Asthana et al () found that cross‐listed firms, with smaller size and more international incomes, are more inclined to choose US‐based Big N auditors rather than Big N auditors based on their home countries. Moreover, the propensity for choosing US‐based Big N auditors decreases with an increase in the investor protection environment of the home country of cross‐listed firms.…”
Section: Determinants Of Auditor Choicementioning
confidence: 99%
See 3 more Smart Citations